Vivências e Experiências de Professores da Educação Infantil da Rede Pública Municipal de Anápolis-go com Crianças com Transtorno do Espectro Autista - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The experiences that cross the teaching profession can unveil important strategies to be applied in pedagogical practice. They highlight the importance of critical reflection for teaching and learning. This research is located in the research line “Education, School and Technologies” and in the thematic axis “Educational Processes and Diversities”, of the Interdisciplinary Graduate Program in Education, Languages and Technologies, of the State University of Goiás. The research has the participation of teachers who work in Early Childhood Education, in municipal public schools of Anápolis/GO and has as its theme the inclusion of children with Autism Spectrum Disorder (ASD). To explore the theme, we defined the following research question: what reflections and findings emerge from the experiences of teachers who work in Early Childhood Education in the municipal public- school network of Anápolis/GO with children with ASD? To answer the question, we set the following general objective: to unveil the experiences of teachers who work in Early Childhood Education in the municipal public-school network of Anápolis/GO with children with ASD and, as specific objectives, are: (a) to understand Early Childhood Education in the municipal public-school network of Anápolis/GO from the perspective of inclusive education; (b) to understand the process of training teachers of Early Childhood Education in the municipal public-school network of Anápolis/GO; and (c) to identify, in the narratives of Early Childhood Education teachers from the municipal public-school network of Anápolis/GO, intrinsic and extrinsic aspects regarding the inclusion of children with ASD. The justification for this research lies in its contribution as a source for reflection on the inclusion of children with ASD. The authors who make up the theoretical basis for the work are Kramer (2016) and Teixeira and Araújo (2016), Cunha (2013; 2020), Pacheco (2007), Macedo (2021), Imbernón (2011) and Laureano (2017). The research is characterized by a qualitative approach, evidencing the expectations, beliefs, convictions and insecurities that are part of this context. To this end, interviews were used as an instrument for data collection, whose analysis was close to the phenomenological method, seeking the subjectivity of the pedagogical paths, as well as the challenges and successes perceived and experienced in their professional trajectory through narratives. The teachers’ testimonies enabled a deeper understanding of the challenges inherent in the daily interaction of children with ASD in the school context. Such reports revealed from the initial apprehension of the teachers in the face of the lack of knowledge about the spectrum, to the progressive development of affective bonds with the child throughout the school year.
Experiences of early childhood education teachers from the municipal public-school network of Anápolis/GO with children with autism spectrum disorder
Keywords: Educação infantil - Inclusão escolar; Transtorno do Espectro Autista; Formação de Professores - Rede Pública de Ensino; Early Childhood Education - School Inclusion; Autism Spectrum Disorder; Teacher Training - Public School System; CIENCIAS HUMANAS::EDUCACAO; FUNDAMENTOS DA EDUCACAO::PSICOLOGIA EDUCACIONAL